Some reflections on the future of the water quality of the corumbataí River basin, São Paulo state, Brazil - Bonotto, Daniel Marcos [UNESP]; De Lima, Jorge Luis Nepomuceno (My University, 2007)
The waters of Corumbataí River in the middle and eastern part of São Paulo State, Brazil, are extensively used for human consumption; their water quality has been modified mainly due to increasing pressure caused by population growth, accompanied by a more accentuated industrial development for the whole São Paulo State in the early 1970s. The Corumbataí River basin has, over time, received significant emissions of municipal waste products and discharges of wastewater, sludge, sewage, sanitary and industrial effluents, but the first effluent treatment plant at Rio Claro city was only inaugurated at the end of the 1990s. Data on river water quality from two widely spaced locations in the Corumbataí River basin are reported in this paper; they indicate the need for continuous initiatives and efforts by decision makers in order to improve and preserve the water quality in the basin for the 21st century. Copyright © 2007 IAHS Press.
Keywords: Corumbataí river basin; Physical and chemical parameters; Rainwater; Surface water; Water quality; Earth sciences; Effluent treatment; Forecasting; Industrial emissions; Industrial waste treatment; Population statistics; Rivers; Sedimentation; Sedimentology; Sewage; Sewage treatment; Waste treatment; Wastewater; Wastewater treatment; Water treatment; Watersheds; 21st centuries; Decision makers; Effluent treatment plants; Human consumptions; Industrial developments; Industrial effluents; Municipal wastes; Population growths; River basins; River water qualities; Effluents; decision making; rainwater; river; surface water; waste disposal; water quality; Brazil; Corumbatai Basin; Sao Paulo [Brazil]; South America